New records of rarely reported species in the Mediterranean Sea (July 2023) - DANIELE GRECH; EMANUELE ASCIUTTO; RIGERS BAKIU; PIETRO BATTAGLIA; CHAIMA BEN-GRIRA; ÖZNUR YAZILAN ÇAMLIK; ROBERTO CAPPUCCINELLI; LEILA CARMONA; SAHAR CHEBAANE; FABIO CROCETTA; ANDREA DESIDERATO; FILIPPO DOMENICHETTI; et al. (Mediterranean Marine Science, 2023)
This Collective Article presents new information about the occurrence of 23 marine taxa that belong to five Phyla: two Chlorophyta, one Annelida, six Mollusca, three Arthropoda, eleven Chordata (one Ascidiacea, one Elasmobranchii and nine Teleostei) and extending from the Western Mediterranean to the Levantine Sea. All these records were reported from nine countries from the western to the eastern Mediterranean Sea, with a broad biogeographical coverage as follows: Spain: first records of the sacoglossans Cyerce graeca and Placida tardyi for the Alboran Sea and first records of the nudibranch Marionia gemmii for the Mediterranean waters of Spain; first records of nudibranch Algarvia alba in the Mediterranean Sea. Italy: First report of the long-legged crab Paragalene longicrura, a further new Mediterranean record of the rare offshore rockfish Pontinus kuhlii, first documented record of the spiny butterfly ray Gymnura altavela in Sardinia (Tyrrhenian Sea), new record of the red‐spotted wrasse Lappanella fasciata from the Messina Strait, first documented record of the rarely observed brown moray Gymnothorax unicolor in the Ionian coast, first record of the colonial ascidian Botrylloides israeliensis, first record of the Morocco dentex Dentex maroccanus, first record of mottled shore crab Pachygrapsus maurus and of an adult specimen of barracudina Lestidiops sphyrenoides in the Adriatic Sea, and further new Mediterranean records of Ross worm Sabellaria spinulosa along the same coast. Tunisia: second record of smalleye squaretail Tetragonurus cuvieri from the African Mediterranean coast. Slovenia: first records of the sea slug Trapania graeffei and Melanochlamys wildpretii, with the last one also representing the northernmost finding of this species. Croatia: northernmost record of the endangered twaite shad Alosa fallax in the Adriatic coast. Albania: first records of the Mediterranean spearfish Tetrapturus belone. Türkiye: first record from the Aegean coasts for Türkiye of the green macroalgae Cladophora battersii and Valonia aegagropila. Israel: first record of the skeleton shrimp Caprella acanthifera in the Southeastern Mediterranean Sea. Syria: first record of the Smooth grenadier Nezumia aequalis from Syrian marine waters.